A new species of Acroperus Baird, 1843 (Cladocera: Chydoridae) from Africa - Neretina, Anna N.; Kotov, Alexey A. (Zootaxa, 2015)
A new species of Acroperus Baird, 1843 (Cladocera: Chydoridae) is described based on the material from Lake Tana, Ethiopia and two water bodies in Eastern Cape, Republic of South Africa. In Africa, Acroperus africanus sp. nov. had a chance to be confused by previous authors with Palearctic A. harpae (Baird, 1834) and A. angustatus Sars, 1863, but it could be easily distinguished from the latter by: (1) smaller seta on the proximal segment of antenna II endopod; (2) larger values of seta 3/seta 2 length ratio on the limb I, as well as some additional features. Diversity of the genus in Africa is underestimated yet, and further investigations of taxon distribution and ecology are necessary.